Multimodal imaging and photothermal/chemodynamic therapy of cervical cancer using GSH-responsive MoS2@MnO2 theranostic nanoparticles - Runrun Shao; Xiaofang Qiao; Linlin Cao; Jianliang Man; Lingyun Guo; Lanlan Li; Wen Liu; Lihong Li; Bin Wang; Lixia Guo; Sufang Ma; Boye Zhang; et al. (Discover Nano, 2023)
Abstract The development of nanoparticles capable of inducing reactive oxygen species (ROS) formation has become an important strategy for cancer therapy. Simultaneously, the preparation of multifunctional nanoparticles that respond to the tumor microenvironment is crucial for the diagnosis and treatment of tumors. In this study, we designed a Molybdenum disulfide (MoS2) core coated with Manganese dioxide (MnO2), which possessed a good photothermal effect and could produce Fenton-like Mn2+ in response to highly expressed glutathione (GSH) in the tumor microenvironment, thereby generating a chemodynamic therapy (CDT). The nanoparticles were further modified with Methoxypoly(Ethylene Glycol) 2000 (mPEG-NH2) to improve their biocompatibility, resulting in the formation of MoS2@MnO2-PEG. These nanoparticles were shown to possess significant Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) imaging capabilities, making them useful in tumor diagnosis. In vitro and in vivo experiments demonstrated the antitumor ability of MoS2@MnO2-PEG, with a significant killing effect on tumor cells under combined treatment. These nanoparticles hold great potential for CDT/photothermal therapy (PTT) combined antitumor therapy and could be further explored in biomedical research.